Nondestructive bending strength testing of wood wool cement board from some fast growing species using stress wave velocity method - Lina Karlinasari; Muhammad F Ikhsan; Dede Hermawan; Akhiruddin Maddu; Anita Firmanti (Jurnal Ilmu dan Teknologi Kayu Tropis, 2011)
The nondestructive testing using stress wave velocity method is known as most important tool to be used in quality control purposes. The aim of this study was to investigate the stress wave velocity (SWV) and to determine correlation between its velocity and dynamic MOE on static bending strength properties (MOE and MOR) of wood wool cement particleboards (WWCB). Thirty six WWCB particleboards from 3 tropical fast growing species (Paraserianthes falcataria, Maesopsis eminii, and Acacia mangium) and three different particleboards density of 0.5, 0.8 and 1.0 g cm-3 were made in this study. SWV value was determined using stress wave timer and it used to measure dynamic MOE. The measurement results of static bending strength method (MOEs and MOR) and by stress wave method were compared. The result showed the higher density of CBWW the higher of stress wave velocity. The WWCB particleboard of sengon possessed the highest value for both SWV and MOR. The dynamic MOE measured by stress wave method was about 80% higher than that static test. The good correlations were found between SWV and static MOE, MOR and it was statistically significant for linear regression model developed.Key words: fast growing species, nondestructive testing, static bending strength, stress wave velocity, wood wool cement particleboard